A new organic redox species-indole tetraone trapped MWCNT modified electrode prepared by in-situ electrochemical oxidation of indole for a bifunctional electrocatalysis and simultaneous flow injection electroanalysis of hydrazine and hydrogen peroxide. (1st April 2018) - Mayuri, Pinapeddavari; Huang, Sheng-Tung; Mani, Veerappan; Kumar, Annamalai Senthil
Abstract: Indole and its derivatives are important core constituents of several natural, biological and pharmaceutical relevant compounds. In general, electrochemical oxidation of indole on solid electrodes in acid and non-aqueous conditions results in the formation of polyindole like compounds as an end product. Selective and controlled electrochemical oxidation of indole and its derivatives to redox active intermediate compound/s without over-oxidation to the polymeric product is a challenging research task. Herein, we report an electrochemical oxidation of electro-inactive indole to a multi-redox active Indole Tetraone (1H-Indole-2, 3, 4, 7-Tetraone)-a new organic redox species (Ind-Tetraone) and entrapment as a surface-confined redox active species on multiwalled carbon nanotube modified glassy carbon electrode (GCE/MWCNT@Ind-Tetraone) in physiological pH solution. GCE/MWCNT@Ind-Tetraone showed a well-defined surface-confined redox peaks at E1/2,  −0.270 V (A1 /C1 ) and +0.270 V (A2 /C2 ) vs Ag/AgCl. From the physicochemical characterizations by Raman and IR spectroscopy, XPS, LC-MS (an ethanolic extract) and control electrochemical experiments with various substituted indole derivatives, it is confirmed the formation of Ind-Tetraone species without any polyindole formation upon the electrochemical oxidation of indole on MWCNT surface. Electrochemical oxidation of nitrogen atom as a radical species and subsequent electron-transfer/water addition reaction is proposed as a possible mechanism for the Ind-Tetraone product formation. A simultaneous electrocatalytic oxidation of hydrazine and reduction reaction of hydrogen peroxide at two discreet potentials has been demonstrated as a bifunctional application of the GCE/MWCNT@Ind-Tetraone system. In further, the GCE/MWCNT@Ind-Tetraone as a electrochemical detector, simultaneous flow injection analysis of hydrazine and hydrogen peroxide was also demonstrated as a proof of concept for the bifunctional application. Graphical abstract: Highlights: Indole electro-oxidation reaction is a difficult to perform on solid electrode in normal condition. MWCNT assists conversion of indole to a new redox species, Indole-tetraone without any polymer formation. Ind-Tetraone is never synthesized and is never reported in the literature. Ind-Tetraone@MWCNT showed effective for bifunctional electrocatalysis. A bipotentiostat coupled simultaneous flow injection analysis of hydrazine and H2 O2 demonstrated.